PREVALENCE OF FASCIOLOSIS IN CATTLE AND SHEEP SLAUGHTERED FOR HUMAN CONSUMPTION IN THE WHITE NILE STATE, SUDAN: A RETROSPECTIVE - E. Babiker, Amna; Elmansory,; H.A, Y.; A. Elsadig, Asha; A.,M, Majid (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to determine the prevalence rate of Fasciola gigantica infection in slaughtered cattle and sheep through collection of records during 1998-2007 in the White Nile State, Sudan. Four localities, Kosti, El Jebelein, Ed Dueim and El Geteina slaughterhouses were included in this study. Ranges of 19659 to 37327 heads of cattle and 22215 to 65466 heads of sheep were slaughtered annually during this period. The lowest prevalence rate (4.00%) for F. gigantica infection was reported in cattle in the year 1999 while the highest (10.41%) was recorded in 2000. The lowest prevalence rate (1.38%) in sheep was in 2007 and the highest (3.73%) was in 2002. The overall prevalence rate of F. gigantica infection was higher in cattle (6.05%) compared to sheep (2.37%). The prevalence rate was higher in the wet season compared to the dry and cold season, but the difference was insignificant (p≥0.05). Localities, the prevalence was found to be 9.2% in Ed Dueim, 9.1% in El Jebelein, 6.2% in Kosti and 2.9% in El Geteina for cattle. The prevalence rate in sheep, however, showed no significant difference (p˃0.05) with regard to season or locality